The effectiveness of trunk-supporting seat belt in reducing low back muscle fatigue for sea-port crane operators - S, Kleebprathum; T, Sangiamsak; S, Lormphongs (Biomedical Sciences and Clinical Medicine, 2021)
Objectives To study the effectiveness of trunk-supporting seat belt for reducing low back muscle fatigue. Methods The study used a single group of volunteers to compare the fatigue of lower back muscles between wearing and not wearing a seat belt to support their torso. The comparison was made by first sitting then leaning the torso forward at an angle of 30 degrees for 30 minutes. The lower back muscles were analyzed by using an electromyography (EMG). An EMG potential was measured on the area of the lumbar erector spinae muscles of twenty medical students between September to November 2020. The data were analyzed using statistics (Matched Pair Statistic). Results The group study outcome consisted of 4th and 5th year male medical student volunteers from the academic year of 2020. The volunteers who passed the selection criteria totalled twenty people with an average age of 22.75 years. The median difference in EMG potential measured on the lumbar erector spinae was as follows: When the body support belts were in place and then not in place the results were: 58.0 (42.00 - 121.75) hertz and 16.50 (11.25 - 60.75) hertz, respectively, which showed a significant difference. (Z = -3.921 statistic, p < 0.001). Conclusions The use of seat belts to support the torso can reduce the fatigue of the lower back muscles of a port crane operator. Crane operation requires the torso to be bent forward at times. Muscle fatigue results can be assessed by using an EMG.